Análisis de los Síntomas musculoesqueléticos por posturas ergonómicas inadecuadas de trabajo en estudiantes y profesionales de la facultad de odontología en el segundo periodo del año 2020. (2020)
Introduction. The symptoms of musculoskeletal disorders (SMS) are related to inappropriate ergonomic postures and constitute a large part of occupational diseases in dentistry, the presence of which depends on the preventive measures that each student or graduate assumes in their daily clinical practice. Objective. Describe the symptoms of musculoskeletal disorders associated with inappropriate posture. Methods. Cross-sectional descriptive study of 150 students and 67 graduates of the Antonio Nariño University, Armenia, Bogotá, Bucaramanga, Palmira and Villavicencio branches. Results. In both students and graduates, 94.5% reported having presented SMS as a consequence of clinical practice, whose location with the highest percentage of pain manifested was in the neck and shoulders with 65.9%, followed by pain in the middle back with 15.7%. Inappropriate postures during clinical practice, represented by the 47.8% that they always / frequently perform, increasing per semester of training together with the semester hour intensity. Conclusions. In dental students and professionals at the UAN, the pain that occurs most frequently is in the neck and shoulders in 6 out of 10 respondents. Musculoskeletal symptoms as a product of inappropriate ergonomic work postures occur more in women and for a longer time per day.